UPAYA MENURUNKAN KADAR ASAM URAT PADA LANSIA DENGAN BAMBOO EXERCISE - Santoso, Didit Wahyu; Khusniyah, Zulfa (Jurnal EDUNursing, 2020)
Abstract Gout is the result of results in the body which levels should not be excessive. Bamboo exercise is a nonpharmacological effort that can be done to increase the metabolism and excretion of uric acid through sweat, urine, or feces. The purpose of this study was to study the effect of bamboo exercise on reducing uric acid levels in the elderly. This research is a Pre-Experimental study using the One Group Pretest-Postest Design method. With a population of 41 elderly, getting a sample of 18 respondents with Purposive Sampling techniques. Independent variable is bamboo practice and Dependent variable in this study is uric acid level. Data collection using GCU / Urt Test then the respondent gave 20 minutes bamboo training for 7 consecutive days. Then the results of the study were analyzed using the Paired Sample T-Test with α = 0.05. The results obtained showed a decrease in value before and after on bamboo exercise as much as 0.533. And from the results of the SPSS test, it was found that p = 0.046 (p≤α) which was useful was found between bamboo exercises and decreased uric acid levels. Bamboo training The privilege is that the elderly are more free to move because there is a bamboo balance aid, so that it will increase uric acid excretion to the maximum. Keywords: Gout, Bamboo Exercise, Elderly.